Characterising the Phenotypic Diversity of Antigen-Specific Memory B Cells Before and After Vaccination - Tjiam, M. Christian; Fernandez, Sonia; French, Martyn A. (Frontiers in Immunology, 2021)
The diversity of B cell subsets and their contribution to vaccine-induced immunity in humans are not well elucidated but hold important implications for rational vaccine design. Prior studies demonstrate that B cell subsets distinguished by immunoglobulin (Ig) isotype expression exhibit divergent activation-induced fates. Here, the antigen-specific B cell response to tetanus toxoid (TTd) booster vaccination was examined in healthy adults, using a dual-TTd tetramer staining flow cytometry protocol. Unsupervised analyses of the data revealed that prior to vaccination, IgM-expressing CD27+ B cells accounted for the majority of TTd-binding B cells. 7 days following vaccination, there was an acute expansion of TTd-binding plasmablasts (PB) predominantly expressing IgG, and a minority expressing IgA or IgM. Frequencies of all PB subsets returned to baseline at days 14 and 21. TTd-binding IgG+ and IgA+ memory B cells (MBC) exhibited a steady and delayed maximal expansion compared to PB, peaking in frequencies at day 14. In contrast, the number of TTd-binding IgM+IgD+CD27+ B cells and IgM-only CD27+ B cells remain unchanged following vaccination. To examine TTd-binding capacity of IgG+ MBC and IgM+IgD+CD27+ B cells, surface TTd-tetramer was normalised to expression of the B cell receptor-associated CD79b subunit. CD79b-normalised TTd binding increased in IgG+ MBC, but remained unchanged in IgM+IgD+CD27+ B cells, and correlated with the functional affinity index of plasma TTd-specific IgG antibodies, following vaccination. Finally, frequencies of activated (PD-1+ICOS+) circulating follicular helper T cells (cTFH), particularly of the CXCR3-CCR6- cTFH2 cell phenotype, at their peak expansion, strongly predicted antigen-binding capacity of IgG+ MBC. These data highlight the phenotypic and functional diversity of the B cell memory compartment, in their temporal kinetics, antigen-binding capacities and association with cTFH cells, and are important parameters for consideration in assessing vaccine-induced immune responses.